(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this study we will discuss about the Study of Ecology and Phytogeography Namibia Is Divided into Nine Phytogeography Groups, Based Exclusively on Distribution Patterns of Plant Species. Results Are Presented In The Form Of A Map Based On Representative Species From Each Of The Nine Groups. The Characteristics, Floristic Composition And Relationships Of Each Group Are Presented. Conceivable Ecological And Historical Causes For These Divisions Are Discussed. Proof From Studies Of The Palaeo-Environment Proved To Be Of Little Use, But (Pan-) Phytogeographic Relationships Of The Extant Flora Provided Clues, Along With Climate And Topography Was Introduced In Indian Subcontinent Dating Back To 1800s As An Ornamental Plant. Maxent, As Regards To Their Ability To Predict The Geographic Distributions Of Species. The Results Mirror The Known Distribution Of The Lantana Camara Fairly Well With Various Degrees Of Predictions. Maxent Succeeded In Anticipating Most Of The Invasion Potential Distributions Whereas GARP And Biomapper Produced An Odd Pattern Of Over-Predictive And Under-Predictive Models Respectively. These Findings Are Relevant As Model Projections Provide A Useful Way To Visualize Spatial Spread And Extent Of Invasion Potential Distribution. Such Predictions Are Useful For Conservation Practices Including Decisions For Early Detection And Formulation Of Targeted And Timely Mitigation Measures To Curb Invasion.